Faktor-Faktor Yang Berhubungan Dengan Sistem Manajemen Rumah Sakit Dhealth - Tjiang, Faliani Chandra; Suci Rahmadani; Muh. Yusri Abadi (Homes Journal = Hospital Management Studies Journal, 2024)
Background: Delivering electronic medical records and health transformation, RSUD Labuang Baji implemented the Dhealth Hospital Management Information System (SIMRS). However, this SIMRS has obstacles in terms of human, organization, and technology. Objective: To analyze the relationship of human, organizational, and technological components with the benefits of SIMRS Dhealth at RSUD Labuang Baji. Methods: Quantitative research with a cross sectional study design. The sample was 221 health workers using SIMRS DHealth at Labuang Baji Hospital. Data collection using a questionnaire. Results: System use, user satisfaction, organizational structure, top management support, IT staff capabilities, system quality, information quality, and service quality have a positive relationship with the benefits of SIMRS Dhealth at Labuang Baji Hospital. Conclusion: Users need to routinely use SIMRS. RSUD Labuang Baji needs to improve the network and add IT staff. The SIMRS developer needs to simplify features, improve the system, and provide instructions for use.